ANALISIS ALIH KODE DAN CAMPUR KODE PADA KOMUNITAS DAYAK DI MADIUN DALAM PERCAKAPAN SEHARI-HARI - Gusment, Gusment; Adhani, Agnes (Educatio Vitae, 2017)
This research aims to find code switching and code mixing between bahasa Indonesia and bahasa Dayak Ahe which every student use in Dayak community everyday conversation in Madiun.This research uses descriptive qualitative approach, which based on descriptive data in the form of everdyday conversation.The result of research: code switching from bahasa Indonesia into Dayak Ahe in 10 times, the cause is due to the presence of the third speaker (03). Code switching from bahasa Dayak Ahe into bahasa Indonesia in 11 times, the cause is due to the presence of the third speaker (03) and hearer (02) in internal code switching. Code mixing in bahasa Dayak Ahe into bahasa Indonesia in 12 times, the cause is due to the linguistics background of the speaker. Code mixing in bahasa Indonesia into bahasa Dayak Ahe in 7 times, the cause is due to the linguistics background of the speaker in the form of code mixing in the insertion of elements of word, the insertion of elements of phrase, and the insertion of elements of clause.